ИЗКУСТВЕН ИНТЕЛЕКТ: ГЕНЕРАТИВЕН ИЛИ С ЕКСПЕРТНИ СИСТЕМИ? - АНГЕЛОВА, ДОРОТЕЯ (Philosophical Alternatives Journal / Filosofski Alternativi, 2025)
The article examines the questions, concerning the reliability of knowledge, acquired through artificial intelligence (AI), the quality of the information, extracted from it, i.e. to what extent AI could be regarded as a trustworthy source of knowledge. In this regard, two main types of AI are considered from a more general logical-methodological perspective, namely - artificial intelligence using rule-based expert systems and generative artificial intelligence. Their main characteristics, advantages and disadvantages are presented and analyzed (from a general point of view), which respectively are used to find the answers of the mentioned questions. It is concluded that combining the two approaches will make AI a more reliable source of knowledge, thus it is relevant their combination to become a trend.